Technology and corruption the missing and morbid links of development in Africa - Aneke, Austin (Bloomington Author house, 2012)
Africa is today missing in the technology radar of the world, but very visible in the corruption index. This represents a clear road map to perpetual underdevelopment, subjugation, and perdition. While no country or continent has ever developed without recreating industrial revolution in its own way, African countries, by omission or commission are attempting to develop by embracing corruption and ignoring the revolutionary powers of science and technology. Africa cannot develop without their own well developed science and technology, and cannot develop with the level of corruption in the continent as we know it today. While western nations continue to advise African leaders to stop stealing the AID they send to them, they have never and will never advise them to embrace technology in order to create their own wealth. The author has done a great deal of work exposing the ills of African leaders and their western collaborators which brought Africa to this pitiable state of underdevelopment. Until corruption is greatly minimised in the continent and science and technology embraced; Africa will never achieve sustainable development. No one can do it for Africa except Africans themselves.
Includes bibliographies
Keywords: Technology